Prime Minister Decree No. 22/2104 Concerning The Increase Of Wages = قرار رئيس مجلس الوزراء رقم 22 لسنة 2014 بشأن زيادة الأجور - Egypt; The middle east library for economic services, translator. (2025)
Prime minister decree no. 22 of the year 2014 قرار رئيس مجلس الوزراء رقم 22 لسنة 2014